2021
DOI: 10.1159/000512641
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of XPD and XPF Polymorphisms to Susceptibility of Non-Small Cell Lung Cancer in High-Altitude Areas

Abstract: <b><i>Background:</i></b> We aimed to explore the relation of <i>XPD</i> and <i>XPF</i> variants with non-small cell lung cancer (NSCLC) risk and the effect of these variants on the sensitivity to cisplatin-based chemotherapy among the Chinese Han population in high-altitude areas. <b><i>Methods:</i></b> Eight single-nucleotide polymorphisms (SNPs) in <i>XPD</i> and <i>XPF</i> were genotyped by Agena MassARRAY platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In the present study, XPD silencing enhanced cisplatin sensitivity, and the XPF and XPD gene expression levels correlated with cisplatin resistance in NSCLC cell lines. Consequently, the results of the present study supported the findings of the clinical study of Li et al (34), and suggested that these molecules may be utilized as biomarkers for predicting cisplatin sensitivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, XPD silencing enhanced cisplatin sensitivity, and the XPF and XPD gene expression levels correlated with cisplatin resistance in NSCLC cell lines. Consequently, the results of the present study supported the findings of the clinical study of Li et al (34), and suggested that these molecules may be utilized as biomarkers for predicting cisplatin sensitivity.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Jian et al (33) reported that XPD overexpression significantly increased cisplatin sensitivity, and revealed that XPD regulated the PI3K/AKT signaling pathway in esophageal squamous cell carcinoma, this information also being valuable for the further evaluation of cisplatin resistance. However, Li et al (34) reported that XPD and XPF polymorphisms may contribute to the risk of NSCLC and the response to cisplatin-based chemotherapy in a Chinese population. In the present study, XPD silencing enhanced cisplatin sensitivity, and the XPF and XPD gene expression levels correlated with cisplatin resistance in NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%